2014
DOI: 10.1111/fwb.12391
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of lake occupancy by fish indicate different adaptations to life in a harsh Arctic environment

Abstract: Summary For six fish species sampled from 86 lakes on the Arctic Coastal Plain, Alaska, we examined whether lake occupancy was related to variables representing lake size, colonisation potential and/or the presence of overwintering habitat. We found the relative importance of each factor for a given species could be related to its ecology and adult size. The three large‐bodied migratory species, least cisco (Coregonus sardinella), broad whitefish (Coregonus nasus) and arctic grayling (Thymallus arcticus), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(88 citation statements)
references
References 43 publications
7
79
1
Order By: Relevance
“…spawning substrate and warm temperatures) and food. Regionally, our results are supported by Haynes et al (2014) and Morris (2003), who documented Arctic grayling, least cisco (Coregonus sardinella), broad whitefish (Coregonus nasus) and burbot (Lota lota) using off-channel ephemeral habitats and shallow lakes in the Arctic Coastal Plains. Ephemeral lakes may serve similar functions, since the period of drying (and perhaps freezing) and accumulation of organic materials can precondition these habitats for periods of peak productivity when inundated just like river floodplains (Junk, Bayley & Sparks 1989).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…spawning substrate and warm temperatures) and food. Regionally, our results are supported by Haynes et al (2014) and Morris (2003), who documented Arctic grayling, least cisco (Coregonus sardinella), broad whitefish (Coregonus nasus) and burbot (Lota lota) using off-channel ephemeral habitats and shallow lakes in the Arctic Coastal Plains. Ephemeral lakes may serve similar functions, since the period of drying (and perhaps freezing) and accumulation of organic materials can precondition these habitats for periods of peak productivity when inundated just like river floodplains (Junk, Bayley & Sparks 1989).…”
Section: Discussionsupporting
confidence: 89%
“…Recognising the role of stream-lake linkages can lead to better broad-scale understanding of abundance and distribution patterns of fish in both lakes and streams (Haynes, Rosenberger, Lindberg, Whitman, & Schmutz, 2014;Pépino et al, 2017). For example, considering the presence or absence of a stream connection helped predict the species composition and occupancy of fish in Arctic lakes (Haynes et al, 2014;Laske et al, 2016).…”
mentioning
confidence: 99%
“…We found that the strongest peak in within-stream movement was during the spring flooding period in both years, suggesting that this annual and relatively predictable event is a critical period for Arctic grayling dispersal and seasonal habitat access. Our observations support the conceptual model of the role of flood dispersal in Arctic lakes by Haynes et al (2014).…”
Section: Migration and Movementsupporting
confidence: 86%
“…For example, low water conditions, freezing, and anthropogenic disturbance can limit movement between habitats and have pronounced ecological effects at individual, population, and metapopulation levels (Labbe and Fausch 2000;Fagan 2002). Alternatively, periodic flooding can connect formerly isolated habitats allowing for dispersal and gene flow among metapopulations (Schlosser and Angermeier 1995;Haynes et al 2014). Thus, mechanistic explanations of fish movement in rivers and streams should include environmental variation as it may mediate both habitat connectivity and relative differences in habitat quality through time.…”
Section: Introductionmentioning
confidence: 99%
“…sardinella , with a mixture of migratory and resident individuals, especially on the Arctic coastal plain. A recent model of fish occupancy in lakes on the Arctic coastal plain provides further support of this variation in life histories, with resident fishes selecting deep‐water refugia in which to overwinter and migratory fishes selecting lakes closer to the coastline, where lakes act as migratory stepping stones to marine waters (Haynes et al , ). Although some variation is shared among the three regions identified, not enough variation is maintained among regions to consider Alaskan C .…”
Section: Discussionmentioning
confidence: 99%